QoS routing for Cognitive Radio Ad-Hoc Networks: Challenges & issues - Malik, T.S. (Institute of Electrical and Electronics Engineers Inc., 2014)
Cognitive Radio Ad-Hoc Network (CRAHN) is an emerging class of mobile ad hoc networks that provides each network node with a list of available channels. It is expected that the available routing protocols and metrics for traditional ad-hoc networks are not suitable for CRAHN in the environment of topology changes and different level of user mobility interference situations. Therefore, to achieve more realistic cognitive routing in radio ad hoc networks, routing metrics and routing protocols should be designed to adapt to traffic and propagation conditions. The focus of this work is on highlighting such routing metrics which are emphasizing on the implementation and improvement of the traditional routing protocols in case of channel switching and user mobility. The aim of any routing protocol is to provide the basic Quality of Service (QoS) to the applications in terms of overall throughput and end-to-end delay. We have simulated the basic routing protocols in traditional ad hoc network and CRAHN environments using NS-2 on the current available routing metrics and results highlighted that there are some challenges and issues are still open to provide the QoS routing in CRAHN environment. Â© 2014 IEEE.